Immune response-eliciting exposure to Campylobacter vastly exceeds the incidence of clinically overt campylobacteriosis but is associated with similar risk factors: A nationwide serosurvey in the Netherlands. Issue 3 (September 2018) - Monge, Susana; Teunis, Peter; Friesema, Ingrid; Franz, Eelco; Ang, Wim; van Pelt, Wilfrid; Mughini-Gras, Lapo
Highlights: Campylobacter seroincidence was 1.6 per person-year and seroprevalence was 68%. This is ∼285 times higher than the incidence of clinical cases. Risk factors for exposure were similar to those for clinical cases. Exposure to Campylobacter was higher in adults, but clinical cases peak in children. These methods provide a precise, easy to interpret way to analyze serological data. Summary: Background: We aimed to estimate population-level exposure to Campylobacter and associated risk factors, using three approaches for serological data analysis. Methods: Nationwide, population-based serosurvey in the Netherlands (Feb 2006–Jun 2007). Anti- Campylobacter IgG, IgM and IgA were measured using ELISA, and analysed via: a) seroincidence estimation, using reference values of antibody peak levels and decay rates over-time after Campylobacter exposure; b) two normal distributions of true positives/negatives fitted to the IgG distribution to derive seroprevalence and individual probability of being positive/negative; and c) IgG levels. Risk factors were analysed using multiple linear regressions. Results: From 1559 respondents, seroincidence was estimated at 1.61 infections/person-year (95%CI:1.58–1.64) and seroprevalence at 68.1% (65.4–70.9). The three approaches identified similar risk factors, although seroincidence had higher power and results were interpretable as risk: seroincidence was higher in females [exp(b) = 1.07(1.04–1.11)], older ages [vs. 15–34 years; for < 5, 5–14, 35–54 and 55–70 years: 0.60(0.58–0.63), 0.74(0.71–0.78), 1.08(1.03–1.13) and 1.08(1.01–1.16), respectively], non-Dutch background [Moroccan/Turkish: 1.25(1.14–1.37); Caribbean: 1.14(1.03–1.25)], low socioeconomic status [1.05(1.01–1.10)], traveling outside Europe [1.05(1.01–1.09)], and eating undercooked meat [1.04(1.01–1.08)]. Conclusion: Campylobacter exposure is much higher than clinical infection rates, but risk factors are similar to those previously described.Seroincidence is a powerful measure to study Campylobacter epidemiology, and is preferred over other methods.